Principal's Strategy in Overcoming Teaching and Learning Problems at SMAN 9 Tana Toraja - Roberto Patabang Allolangi; Andi Agustang (Universitas of Muhammadiyah Makassar, 2022)
Educators as human resources in schools have a very decisive role and are the key to achieving educational goals. The focus of this research problem is how is the principal's strategy to overcome: educators who often give notes to students while the educators concerned hang out outside the classroom?; educators who are not compact?; readiness of learning tools by educators?; Do students hang around a lot during class hours? Research method: observation, interview, documentary. Findings: 1. educators often give notes to students because the classroom atmosphere is boring, students act a lot less respecting educators, the principal does not supervise educators, teaching materials are lacking, and teaching staff is not by their basic education; 2. lack of communication between educators, rare family meetings, jealousy between fellow educators; 3. almost all educators copy the learning tools of other educators; 4. lack of supervision, picket educators are less active in controlling the situation at school. Conclusion: homerooms need to organize classrooms neatly, maintain cleanliness, and discipline students, principals must control regularly, make joint rules about discipline in class, when educators carry out the teaching and learning process HP is disabled, fulfillment of facilities and infrastructure, holding training, 2. Holding family meetings; 3. educators make their learning tools or through MGMP; 4. The picket works according to the task.Tenaga pendidik sebagai sumberdaya manusia yang ada di sekolah mempunyai peranan yang sangat menentukan dan merupakan kunci keberhasilan dalam mencapai tujuan pendidikan. fokus masalah penelitian ini adalah bagaimanakah strategi kepala sekolah mengatasi: tenaga pendidik yang sering memberikan catatan kepada peserta didik sedangkan tenaga pendidik yang bersangkutan nongkrong di luar kelas?; tenaga pendidik yang tidak kompak?; kesiapan perangkat pembelajaran oleh tenaga pendidik?; peserta didik banyak berkeliaran pada saat jam pelajaran sedang berlangsung?. Metode penelitian: observasi, wawancara, dokumenter. Temuan: 1. tenaga pendidik sering memberikan catatan kepada peserta didik karena suasana kelas memjenuhkan, peserta didik banyak bertingkah kurang menghargai tenaga pendidik, tenaga pendidik kurang diawasi oleh kepala sekolah, bahan ajar kurang, serta tenaga pendidik yang mengajar tidak sesuai dengan dasar pendidikannya; 2. kurang adanya komunikasi antara tenaga pendidik, jarang diadakan pertemuan kekeluargaan, adanya rasa kecemburuan antara sesama tenaga pendidik.; 3. hampir semua tenaga pendidik menjiblak perangkat pembelajaran tenaga pendidik lain.; 4. kurangnya pengawasan, tenaga pendidik piket kurang aktif mengontrol keadaan di sekolah. Kesimpulan: wali kelas perlu untuk menata ruang kelas dengan rapi, menjaga kebersihan serta mendisiplinkan peserta didik, kepala sekolah harus mengontrol secara rutin, membuat peraturan bersama tentang tata tertib di kelas, pada saat tenaga pendidik melaksanakan proses belajar mengajar HP di non aktifkan, pemenuhan sarana dan prasarana, mengadakan diklat, 2. Mengadakan pertemuan kekeluargaan.; 3. tenaga pendidik membuat perangkat pembelajaran sendiri atau melalui MGMP.; 4. Piket berkeja sesuai dengan tugas.